Facets of Serendipity in Everyday Chance Encounters: Content Analysis of Social Media Accounts - Rubin, Victoria L.; Burkell, Jacquelyn; Quan-Haase, Anabel (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2013)
This paper analyzes naturally occurring descriptions of chance encounters as found in blogs. We develop a model of serendipity that describes facets of the phenomenon and their interconnections, and examine the applicability of this model to accounts of everyday chance encounters. Cet article analyse les occurrences naturelles des descriptions de hasard trouvées dans les blogues. Nous avons conçu un modèle de serendipité décrivant les facettes du phénomène et leurs interconnections, et avons examiné l’applicabilité du modèle aux cas de hasard courants.